(untitled) (International Journal of Environmental Sciences, 2025)
Potential next-generation electronic applications The combination of these unique quantum confinement effects and optoelectronic tunability has rendered perovskite nanofilms a promising type of next-generation electronic applications. The given work examines the role of quantum confinement in self-assembled organometal halide perovskite nanofilms and tests their applicability to spintronic uses at room temperatures. We constructed well-ordered nanofilms of methylammonium lead halide (MAPbX 3 ; X = Cl, Br, I) using a solution-phase synthesis strategy combined with atomic layer deposition methods and high-resolution electron microscopy. We attained comparable thin films, with thickness in the 520 nm span. The photoluminescence spectra, energy-dispersive X-ray spectroscopy (EDX) and magnetoresistance measurements were performed to measure the band gap shifts and shift in the spin coherence, and the magnetic field response. The motion picture took place on the indices of blue shifts in bandgap energies against decreased thickness, displaying the fact of strong quantum confinement. Besides, spin-polarized transport and anisotropic magnetoresistance in ultrathin MAPbI 3 films were also detected, signifying strong spintronic properties in the ambient. Such results indicate that controlled synthesis of perovskite nanofilm with engineered dimensionality and strain engineering may offer an expedient route to highly cost-effective, low-power spintronic devices. This article sheds light over the structural, electronic and magnetic coupling of confined perovskite layers and presents a framework to integrate them in nanoscale spin-based transistors and memory systems.